Conditions of governance for decision making in the face of environmental issues: the case of Puelo, Cochamó (Revista LIDER, 2019)
In Chile there is an environmental institutionality oriented at comply with international standards. However, there are weaknesses that cause insufficient progress in environmental protection and sustainable development. Being the local territories who live with the negative consequences of this. In this sense, the investigation of the projects entered into the SEIA opens the possibility of better understanding the role of the municipalities and citizen participation in the environmental evaluation processes of the governmental institutionality. Then, it is worth asking: Do the governance systems of the communes of the country have conditions to proactively participate in the environmental impact assessment process of non-conventional renewable energy projects of the SEIA?. Supported by the framework of Project FONDECYT No 1181282, this exploratory case study, which includes the review of different secondary sources and the corresponding content analysis of each of these, proposes that one of the main conditions that local governance systems must have is that evaluation procedures must conform to the temporal dimension of the participation of the different social actors. Being the discrepancy between the possibilities of participation and the times related to the evaluation procedures a challenge for environmental governance in the territory.